A violência entre jovens e adolescentes de Varginha: um olhar interdisciplinar dos fatores precipitantes e os desafios para as políticas públicas - Ôngaro, Maria Emília (2017)
This work it’s the result of doctorate research, which theme is the violence between teenagers and young people in Brazil, and the factors that contribute to this increase in this age group. Starting with the hypothesis that the junction of several factors it’s responsible for the violence increase, in other words, didn't existing, for this increase, just one reason for a complex network of factors. The research it’s constituted, in a first moment, by the theoretical discussion about the violence and the youth, as well as the analysis about the rule of law and the use of institutional force, beyond to official statistics about crime in Brazil and the mass incarceration. The second part of this research contemplates the spatial universe of the city of Varginha, their development and the numbers that compose the social diagnosis and the crime statistics. First in the age universe of 12 to 17 years old, followed by18 to 29 years old and over thirty years old, being able to compare if the increase in violence, in the city, can be found it in the age universe youth. For this, ware lifted the data by means of police occurrences from the year of 2011 to 2015, statistics about teenagers that complied socioeducative measure until august 2016 and the numbers of the prison system of Varginha in which the analyzes indicated about the types of crime, schooling, ethnicity, genre, age and naturalness of the authors. The third part of this research it’s constituted by a foray in the universe of this authors and their families, looking for, by means of a systematic interlocution with Young people which conflicted with the law, to understand the reasons for this conflict. The result is composed of a structure that highlights domestic violence, school exclusion and the increment of the narcotics trade as a preceptors factors and multipliers of violence